2005
DOI: 10.1111/j.1365-2664.2005.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerial photographs as a tool for assessing the regional dynamics of the invasive plant speciesHeracleum mantegazzianum

Abstract: Summary 1.The initiation of an invasion event is rarely dated in studies of alien plants. Data from aerial photographs documenting the invasion from the outset facilitate the quantification of the rate of spread, allowing researchers to analyse species' population dynamics and providing a basis for management. 2. For 10 sites invaded by Heracleum mantegazzianum in the Slavkovsk y les, Czech Republic, aerial photographs from 11 sampling dates between 1947 (before invasion started) and 2000 were analysed. The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
109
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 53 publications
3
109
1
Order By: Relevance
“…Remotely sensed distribution maps have been cited as one of the most accurate methods for estimating spread (Hastings et al 2005). All remote sensing of invasive plant species spread to date has used aerial photography, typically analyzed by manual photointerpretation, due to the length and value of the photo record (Lonsdale 1993, Brown and Carter 1998, Higgins et al 2001, Buckley et al 2005, Mu¨llerova´et al 2005, Maheu-Giroux and de Blois 2007, Browning et al 2008. However, the limitations of photointerpretation restrict analyses to species that are broadly different from the invaded communities, for example, to shrub encroachment of deserts and grasslands (Brown andCarter 1998, Browning et al 2008), pine invasions (Higgins et al 2001, Buckley et al 2005, and species with vivid floral displays (Mu¨llerovaé t al.…”
Section: Introductionmentioning
confidence: 99%
“…Remotely sensed distribution maps have been cited as one of the most accurate methods for estimating spread (Hastings et al 2005). All remote sensing of invasive plant species spread to date has used aerial photography, typically analyzed by manual photointerpretation, due to the length and value of the photo record (Lonsdale 1993, Brown and Carter 1998, Higgins et al 2001, Buckley et al 2005, Mu¨llerova´et al 2005, Maheu-Giroux and de Blois 2007, Browning et al 2008. However, the limitations of photointerpretation restrict analyses to species that are broadly different from the invaded communities, for example, to shrub encroachment of deserts and grasslands (Brown andCarter 1998, Browning et al 2008), pine invasions (Higgins et al 2001, Buckley et al 2005, and species with vivid floral displays (Mu¨llerovaé t al.…”
Section: Introductionmentioning
confidence: 99%
“…Using aerial photographs from 11 sampling dates between 1947 (before H. mantegazzianum invasion started) and 2000, Müllerovà et al (2005) found that pastures and fields contributed 84.7 % to Heracleum total cover, forest and shrub 13.7% and human settlements 1.6 % at later stages of invasion. The authors found that as invasion proceeded, the populations spread from linear habitats to the surrounding landscape with the mean rate of aerial spread of 1,261 m 2 per year and linear spread of 10.8 m per year.…”
Section: Mechanism Of Invasion and Ecosystem Attribute That Can Be Momentioning
confidence: 99%
“…Müllerová et al, 2013;Jones et al, 2011). Detection of herb species is only possible if the data provide enough spectral and/or spatial details, the species are distinct from their neighborhood, form dense and uniform stands, and/or are large enough to be detected (Maheu-Giroux and de Blois, 2004;Müllerová et al, 2005). The potential for invasive species monitoring using RS is still not fully exploited and for the majority of invasive species there are no detection algorithms described.…”
Section: Introductionmentioning
confidence: 99%